Analysis on necessity of community health service development based on limits-to-growth archetype: —taking Jiangxi province as an example. Issue 2 (1st June 2013) - Li, Liqing; Zhou, Xiaojun
Abstract : Objective: To analyze the necessity of community health service (CHS) development in Jiangxi province based on the current status of healthcare in Jiangxi Province. Method: The study did a systematic survey on the CHS development among health service organizations in Jiangxi province. The data of the survey were analyzed with system archetype analysis of Peter Senge. Results: Through system analysis, four limits-to-growth archetypes were built and analyzed. The obstacles restricting the development of healthcare systems were determined, and some effective countermeasures were proposed accordingly. Conclusion: In order to foster the sustainable development of healthcare in Jiangxi province and alleviate the problem of "difficulty and high cost to access medical services" effectively, the government should place more emphasis on the development of CHS.